Effect of Current Density on the Anodic Behavior of Zircaloy - 2 and Titanium-A Comparative Study - N. N. S. Aparna; Ch. Anjaneyulu (E-Journal of Chemistry)
The kinetics of anodic oxidation of zircaloy-2 and titanium have been studied at current densities ranging from 2 to 12 mAcm-2 at room temperature in order to investigate the dependence of ionic current density on the field across the oxide film. Thickness of the anodic films were estimated from capacitance data. The formation rate, current efficiency and differential field were found to increase with increase in the ionic current density for both zircaloy-2 and Titanium. Plots of the logarithm of formation rate vs logarithm of the current density are fairly linear. From linear plots of logarithm of ionic current density vs differential field and applying the Cabrera-Mott theory, the half-jump distance and the height of the energy barrier are deduced and compared.